1951
DOI: 10.6028/jres.046.044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the degradation of polyamides

Abstract: Films of polyamides were exposed to heat, ultraviolet radiant energy, and different atmospheric conditions. The degradation products were collected in some cases and analyzed by mass spectrometric techniques. The unexposed and exposed specimens were examined by the following techniques to obtain information concerning the changes in chemical and physical structure of the polymer: infrared absorption, ultraviolet absorption , viscosity of solutions, measurement of dielectric constant and dissipation factor, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1952
1952
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 29 publications
(45 reference statements)
1
27
0
1
Order By: Relevance
“…From the spectra in Figure 6, it is clear PA1 changes extensively when exposed to UVA. The mechanism of polyamide degradation has also been extensively studied [9,10] and results in the formation of a wide array of oxidized products. magnification, (center) a 2-year exposed backsheet with microcracking at 1000X, and (right) 2-year exposed backsheet with microcracking at 3000X Figure 8 below shows spectra of a TPT backsheet from every exposure condition.…”
Section: Accelerated Tests Results and Ftir Analysismentioning
confidence: 99%
“…From the spectra in Figure 6, it is clear PA1 changes extensively when exposed to UVA. The mechanism of polyamide degradation has also been extensively studied [9,10] and results in the formation of a wide array of oxidized products. magnification, (center) a 2-year exposed backsheet with microcracking at 1000X, and (right) 2-year exposed backsheet with microcracking at 3000X Figure 8 below shows spectra of a TPT backsheet from every exposure condition.…”
Section: Accelerated Tests Results and Ftir Analysismentioning
confidence: 99%
“…Long UV light can cause photodegradation in the presence of oxygen, while short UV light can degrade nylon 66 in the absence of oxygen. Bernard et al [21] found little increase in crystallinity on UV irradiation of nylon 66. The UV-irradiated samples were attacked more easily by water and alcohol.…”
Section: Degradation Of Nylon 66mentioning
confidence: 98%
“…Summary Pyrolysis of the nylon fabric causes depolymerization of the polymer, and not cross-linking of the aliphatic polymer chains. The discovery that considerable amounts of ammonia are formed in the pyrolysis of nylon is incompatible with the assumption of Achhammer et al [1] ] that the main reaction mechanism is the breaking of the -NC-bond. The present work shows that the breaking also occurs at the -CH2-CO-bond, and that this reaction should be considered as one of the possible reactions of nylon pyrolysis.…”
Section: Destructive Distillation Of Nylon Fabricmentioning
confidence: 98%